2007 IEEE Power Engineering Society Conference and Exposition in Africa - PowerAfrica 2007
DOI: 10.1109/pesafr.2007.4498051
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Standards for Determining Losses and Efficiency of Three-Phase Induction Motors

Abstract: The efficiency of induction motors has emerged as having the biggest potential in saving energy consumption. This is important to South Africa where energy saving has risen as a major concern. This paper looks at the different motor efficiency standards that are available and attempts to compare them. The paper discusses results obtained from tests done on a 3kW high efficient motor. Three standards used were the CSA-390 a Canadian standard, IEEE 112 an American standard and the new European standard, the IEC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The standards differ mainly in their treatment of the stray losses in an induction machine [16,17]. A detailed comparison of the different efficiency results between the standards was presented in [18]. The Indian standard IS 12615: 2004 was used in the research related to this paper.…”
Section: Die Cast Copper Rotorsmentioning
confidence: 99%
“…The standards differ mainly in their treatment of the stray losses in an induction machine [16,17]. A detailed comparison of the different efficiency results between the standards was presented in [18]. The Indian standard IS 12615: 2004 was used in the research related to this paper.…”
Section: Die Cast Copper Rotorsmentioning
confidence: 99%
“…The common needs of different size companies to reduce the electricity consume and the costs lead to the use of higher efficiency induction motors. Other consequences like the reduction of CO 2 emission are taken into account too [2,3]. The electrical machines are the main consumers in the industrial sector with an electrical consumption up to 70% of the total consumed energy.…”
Section: Introductionmentioning
confidence: 99%
“…In the last years several studies demonstrated the potential energy saving in the electrical machines can be estimated at about 20% -25%. [4] For this reason the International Electrotechnical Commission (IEC) promulgated the new set of rules IEC 60034-30 in 2007 [2]. The aim of this set of rules is to lead to an unification of the efficiency energetic classes with the scope to make clear the difference among the rules active in the different EU countries [3].…”
Section: Introductionmentioning
confidence: 99%
“…From smaller companies up to bigger multinationals, the target is to reduce the electric energy costs by higher efficiency induction motors [6], [7]. As a consequence, this approach leads not only to a reduction of the energetic bill but also to a reduction of the CO 2 emissions, with solid advantages for the ambient [8]- [ 10].…”
Section: Introductionmentioning
confidence: 99%